2018
DOI: 10.1128/aem.01163-18
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal Plasma Jet Treatment Negatively Affects the Viability and Structure of Candida albicans SC5314 Biofilms

Abstract: Microorganisms are predominantly organized in biofilms, where cells live in dense communities and are more resistant to external stresses than are their planktonic counterparts. With experiments, the susceptibility of biofilms to a nonthermal plasma treatment (plasma source, kINPen09) in terms of growth, survival, and cell viability was investigated. strain SC5314 (ATCC MYA-2876) was plasma treated for different time periods (30 s, 60 s, 120 s, 180 s, 300 s). The results of the experiments, encompassing CFU, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 55 publications
(48 reference statements)
4
30
0
Order By: Relevance
“…Consequently, PTW was generated at the bottom layers of the biofilm and predominantly led to an inactivation in that area. This was also indicated in treatments with the kINPen09 in the same experimental set‐up (Handorf, Weihe et al , ).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Consequently, PTW was generated at the bottom layers of the biofilm and predominantly led to an inactivation in that area. This was also indicated in treatments with the kINPen09 in the same experimental set‐up (Handorf, Weihe et al , ).…”
Section: Discussionmentioning
confidence: 57%
“…Indirect treatment of microorganisms where the effluent has been brought into a short distance over the biofilms is published for plasma jets or DBDs (Maisch, Shimizu et al , ; Khan, Lee et al , ; Handorf, Weihe et al , ). If only the achieved reduction factors are considered for the same treatment time regardless of the type of plasma generation and type of application, RFs of 0.6 for the kINPen09, 2.9 for the hollow electrode dielectric discharge (HDBD) and 2.3 for the volume dielectric discharge (VDBD) were obtained after 1 min treatment time (Koban, Matthes et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main priority is the complete detachment of the biofilm from the overgrown surface to remove it from the system during the flushing processes. Initial studies have already shown a unique effect of plasma gas on the adhering surface of the biofilm [28,29]. The present study aimed to investigate whether PTW also has such special effects on the biofilm.…”
Section: Introductionmentioning
confidence: 95%